Protein Tyrosine Phosphatase Non-Receptor Type 2 Function in Dendritic Cells Is Crucial to Maintain Tissue Tolerance - Hering, Larissa; Katkeviciute, Egle; Schwarzfischer, Marlene; Busenhart, Philipp; Gottier, Claudia; Mrdjen, Dunja; Komuczki, Juliana; Wawrzyniak, Marcin; Lang, Silvia; Atrott, Kirstin; Becher, Burkhard; Rogler, Gerhard; et al. (Frontiers in Immunology, 2020)
Protein tyrosine phosphatase non-receptor type 2 (PTPN2) plays a pivotal role in immune homeostasis and has been associated with human autoimmune and chronic inflammatory diseases. Though PTPN2 is well-characterized in lymphocytes, little is known about its function in innate immune cells. Our findings demonstrate that dendritic cell (DC)-intrinsic PTPN2 might be the key to explain the central role for PTPN2 in the immune system to maintain immune tolerance. Genetic deletion of PTPN2 in DCs resulted in spontaneous inflammation, particularly in skin, liver, lung and kidney 22 weeks post birth. DC-specific PTPN2 controls steady state immune cell composition and PTPN2 deficiency in DCs resulted in enhanced organ infiltration of conventional type 2 DCs, accompanied by expansion of IFNγ-producing effector T-cells. Consequently, the phenotypic effects of DC-specific PTPN2 deficiency were abolished in T-cell deficient Rag knock-out mice. Our data add substantial knowledge about the molecular mechanisms to prevent inflammation and maintain tissue tolerance.